2023
DOI: 10.21203/rs.3.rs-2409162/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Sleeping Brain’s Connectivity and Family Environment: Characterizing Sleep EEG Coherence in an Infant Cohort

Abstract: Brain connectivity closely reflects brain function and behavior. Sleep EEG coherence, a measure of brain’s connectivity during sleep, undergoes pronounced changes across development under the influence of environmental factors. Yet, the determinants of the developing brain’s sleep EEG coherence from the child’s family environment remain unknown. After characterizing high-density sleep EEG coherence in 31 healthy 6-month-old infants by detecting strongly synchronized clusters through a data-driven approach, we … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…For instance, a twin study with adolescents showed that environmental impact could account for 66% (compared to 19% for genetic) of the variance in EEG coherence ( Markovic et al, 2021 ). Although infants have had a shorter exposure to the environment, the family environment still contributes to variability that can be reflected in brain connectivity and, therefore, in the sleep EEG ( Markovic et al, 2023 ). Indeed, beyond the sleep EEG, behavior can also be influenced by the immediate environment.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a twin study with adolescents showed that environmental impact could account for 66% (compared to 19% for genetic) of the variance in EEG coherence ( Markovic et al, 2021 ). Although infants have had a shorter exposure to the environment, the family environment still contributes to variability that can be reflected in brain connectivity and, therefore, in the sleep EEG ( Markovic et al, 2023 ). Indeed, beyond the sleep EEG, behavior can also be influenced by the immediate environment.…”
Section: Discussionmentioning
confidence: 99%